Trends in high arctic muskox (Ovibos moschatus) harvest, 1990-2015 - Morgan Anderson (Rangifer, 2017)
Harvest reporting has been in place for High Arctic muskoxen in Nunavut, Canada, since 1990-91. The communities of Resolute, Grise Fiord, and Arctic Bay harvest muskoxen in the region. Overall, muskox harvest has declined in Resolute and Grise Fiord since the 1990s. The recovery of Peary caribou populations on the Bathurst Island Complex, which provides an alternate preferred source of country food, may be a factor behind Resolute’s decreased muskox harvest. The proportion of harvest for domestic use has also declined relative to sport hunts, which have remained relatively constant since the 1990s. We compared muskox harvest from tag records and reported harvest, i.e., the voluntary surveys to the Nunavut Wildlife Harvest Study for muskoxen. It is clear that voluntarily reported harvest underestimates actual harvest, but not consistently enough to predict the actual harvest. Muskox populations are at historic high levels on Bathurst Island, southern Ellesmere Island, and Devon Island and could support more harvest than is currently taken. Changes to Total Allowable Harvests and management unit boundaries in 2015, combined with a decline in the availability of Baffin Island caribou as country food, may result in increased harvest pressure on muskoxen in the High Arctic.